Sympathetic innervation induced by nerve growth factor promotes malignant transformation in gastric cancer - Takefumi Itami; Yukinori Kurokawa; Takaomi Hagi; Shinnosuke Nagano; Rennosuke Nakamoto; Yu Kamakura; Tsuyoshi Takahashi; Takuro Saito; Kazuyoshi Yamamoto; Kota Momose; Kotaro Yamashita; Koji Tanaka; et al. (Scientific Reports)
Abstract Sympathetic nerves regulate nearly all human organs. Their peripheral nerves are present in tumor tissue. Activation of the sympathetic nervous system promotes malignant transformation in several cancers. This study aimed to quantify sympathetic nerve density (SND) in gastric cancer and investigate the relationship between SND and nerve growth factor (NGF) in human clinical samples using immunohistochemistry. Patients with high SND in tumor tissue had significantly shorter survival. High NGF expression in tumor tissue was significantly associated with increased SND and poorer prognosis. In vitro studies demonstrated that nerve elongation of PC12 cells, a model for sympathetic neuron-like cells, was promoted by co-culture with gastric cancer cells expressing high NGF levels whereas nerve elongation was suppressed by NGF knockdown. Furthermore, noradrenaline, a neurotransmitter released from sympathetic nerve endings, induced malignant transformation by promoting epithelial–mesenchymal transition, increasing invasiveness and enhancing the ability of gastric cancer cells to migrate. These findings suggest that gastric cancer with high NGF expression might promote sympathetic innervation within tumor tissue, fostering malignant transformation through noradrenaline signaling. Thus, suppressing sympathetic nerve elongation or activation in gastric cancer might be a target for new therapeutic interventions.